2020
DOI: 10.3233/jad-190929
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Iron Oxide Nanoparticles Induce Damage to Brain Microvascular Endothelial Cells Forming the Blood-Brain Barrier

Abstract: Background: Iron nanoparticles, mainly in magnetite phase (Fe 3 O 4 NPs), are released to the environment in areas with high traffic density and braking frequency. Fe 3 O 4 NPs were found in postmortem human brains and are assumed to get directly into the brain through the olfactory nerve. However, these pollution-derived NPs may also translocate from the lungs to the bloodstream and then, through the blood-brain barrier (BBB), into the brain inducing oxidative and inflammatory responses that contribute to neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Suwannasual et al showed that exposure to a mixture of gasoline and diesel vehicle engine emissions (MVE) led to alterations in BBB integrity (reduced TJs, upregulated IL-6, TGF-β) via Angiotensin-AT1 signalling and inflammation [228]. Similar effects on TJs were observed with environmental pollutant exposures such as perfluorooctane sulfonate [229] and pollution derived Fe 3 O 4 nanoparticles [230]. Severe BBB dysfunction in children has been observed on exposure to dioxins such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) [231] and fine particulate matter (PM2.5) [232].…”
Section: Environmentmentioning
confidence: 93%
“…Suwannasual et al showed that exposure to a mixture of gasoline and diesel vehicle engine emissions (MVE) led to alterations in BBB integrity (reduced TJs, upregulated IL-6, TGF-β) via Angiotensin-AT1 signalling and inflammation [228]. Similar effects on TJs were observed with environmental pollutant exposures such as perfluorooctane sulfonate [229] and pollution derived Fe 3 O 4 nanoparticles [230]. Severe BBB dysfunction in children has been observed on exposure to dioxins such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) [231] and fine particulate matter (PM2.5) [232].…”
Section: Environmentmentioning
confidence: 93%
“…Synthetic nanoparticles, tiny-engineered structures with wide-ranging applications, are categorized according to their Nanoparticles interact uniquely with biological systems due to their small size and large surface area. While beneficial for medical applications, these interactions raise health concerns (Garate-Velez et al, 2020;Thompson, 2018). For instance, inhaled nanoparticles can penetrate the lungs and nasal mucosa, accessing the central nervous system (CNS) and potentially causing damage at the cellular and mitochondrial levels, leading to various health issues, including cancer and neurodegenerative diseases (Garate-Velez et al, 2020).…”
Section: Understanding Nanoparticles: Sources Types and Characteristicsmentioning
confidence: 99%
“…While beneficial for medical applications, these interactions raise health concerns (Garate‐Velez et al., 2020; Thompson, 2018). For instance, inhaled nanoparticles can penetrate the lungs and nasal mucosa, accessing the central nervous system (CNS) and potentially causing damage at the cellular and mitochondrial levels, leading to various health issues, including cancer and neurodegenerative diseases (Garate‐Velez et al., 2020). Several studies indicate a link between early‐life nanoparticle exposure and the development of neurodegenerative diseases (Calderon‐Garciduenas et al., 2001, 2003).…”
Section: Literature Search and Data Extractionmentioning
confidence: 99%
“…This leads to the accumulation of IONPs that trigger oxidative and inammatory reactions through the Fenton reaction to cause a variety of health issues. 9 It is becoming more and more likely that excessive amount of iron in certain brain areas like the frontal lobe, temporal lobe, parietal lobe, caudate nucleus, globus pallidus amygdala, cingulate cortex, and putamen contribute signicantly to the pathogenesis of AD and other neurodegenerative illnesses. 10 Although dementia is more common in established nations than in developing ones, it is spreading quickly around the globe.…”
Section: Sohini Goswamimentioning
confidence: 99%